The Use of Various Vegetation Level by Bird Community on Mbarek Spring, Gedangan, Malang - Suparno Suparno; Soemarno Soemarno; Amin Setyo Leksono (Indonesian Journal of Environment and Sustainable Development, 2018)
Study of correlation between vegetation and birds could show how great the impact of Figs (Ficus spp.) towards wildlife. Mbarek spring has a unique microhabitat by Figs. These trees expected to provide a high potential role and benefit related to supporting bird life. This study aims to analyze the use of vegetation by birds in the sphere of Mbarek’s spring microhabitat. Study was held in Mulyosari sub-village, Sumberejo village, Gedangan subdistrict, Malang regency. The study was conducted from 26-29 October 2017. Bird observation point was chosen on Ficus racemosa, known locally as ‘Lo’, which suspected to have a major influence on the presence of birds. Each of observation results were identified, counted, and recorded. Documentation were done incidentally. The results are visualized by descriptive representations of the use of vegetation composition on 4 vegetation classifications : seedling (high = 0-1.5 m), sapling (high≥1.5 m), pole (diameter = 10-20 cm), tree (diameter> 20 cm). Sooty-headed Bulbul (Pycnonotus aurigaster) is the dominant bird during observation. Most of birds observed at the canopy  with the activity of sunbathing. Figs became a favorite location for birds to rest and parenting during the day. Sedges (Cyperus sp.) is the greatest importance on study site.Keywords: Birds, Figs, Mbarek, Sedges